Activity-Based Costing in the Restaurant Industry: What's Past Is Prologue. Issue 2 (2nd July 2016) - Raab, Carola; Zemke, Dina Marie
Abstract : Restaurant managers often do not have a comprehensive understanding of all of the costs involved in operating a successful restaurant, leading to inaccurate, and potentially unprofitable, menu item pricing. One trend in cost analysis is to explore techniques used in other industries, including activity-based costing. A body of work exploring the application of activity-based costing in the foodservice industry has gradually evolved. A review of previous research on activity-based costing in various restaurant segments validates it as a consequential approach that is capable of reducing waste, preserving employment, and producing maintainable profitability in the restaurant industry.